Ambipolar Behavior of a Cu(II)–Porphyrin Derivative in Ternary Organic Solar Cells. Issue 5 (13th January 2023) - Cuesta, Virginia; Vartanian, Maida; Kumar Singh, Manish; Singhal, Rahul; de la Cruz, Pilar; Sharma, Ganesh D.; Langa, Fernando
Abstract : Ternary architecture is a promising strategy to achieve high efficiency in organic solar cells. The alignment of third‐component frontier orbitals with those of donor and acceptor (D and A) is of essential importance. Herein, a new molecule VC11, consisting of a Cu(II)–porphyrin core linked to dicyanovinylene terminal acceptor units through (E)‐1, 2‐di(thiophen‐2‐yl) ethene bridges, is described. The highest occupied molecular orbital and lowest unoccupied molecular orbital values of VC11 are −5.52 and −3.74 eV, respectively, lying between the corresponding values of PBDB‐T donor and Y6 acceptor, compounds used in the construction of the studied devices. The measured electron and hole mobilities reveal similar values, in the order of 10 −4  cm 2  Vs −1, indicating the ambipolarity of VC11, that can be used as donor or acceptor. The organic solar cells (OSCs) based on PBDB‐T:VC11, VC11 :Y6, and PBDB‐T:Y6 show power conversion efficiencies (PCEs) of 10.84%, 7.89%, and 11.98%, respectively. VC11 is utilized along with PBDB‐T and Y6 to form a ternary active layer for assembling bulk heterojunction OSCs affording a remarkable PCE of 15.25%, significantly higher than those obtained for the corresponding binary devices. This enhancement of PCE originates from the additional charge separation offered by a cascaded energy‐level alignment and a fast charge transfer, due the ambipolarity of VC11 . Abstract : A new Cu(II)porphyrin‐based acceptor (A)– π –donor– π –A, denoted as VC11, proves to be an excellent third component in ternary organic solar cells with PBDB‐T and Y6 affording a power conversion efficiency as high as 15.25% owing to the additional charge separation offered by a cascaded energy‐level alignment and a fast charge transfer, due the ambipolarity of VC11 .